Penerapan Algoritma C4.5 untuk Analisis Tingkat Kepuasan Santriwan Santriwati Pesantren Darul Ulum Mambaul Huda - Muhammad Ikhsan Aji; Rakhmat Kurniawan (LPPM STT Terpadu Nurul Fikri, 2025)
Student satisfaction is an important indicator for evaluating the quality of educational services in Islamic boarding schools. Therefore, an analytical method capable of accurately identifying the factors that influence student satisfaction is needed. This study aims to analyze the satisfaction levels of male and female students at Pesantren Darul Ulum Mambaul Huda using the C4.5 algorithm. The C4.5 algorithm is used to build a classification model by calculating entropy and information gain to identify the most influential attributes affecting satisfaction levels. The data used in this research were collected through questionnaires that included several assessment variables, including teaching quality, facilities, services, and discipline. The analysis process consisted of several stages, including data cleaning, calculating entropy and information gain, constructing the decision tree, and evaluating the model’s performance using a confusion matrix. The results show that the C4.5 algorithm achieves high classification accuracy and identifies that teaching quality and boarding school facilities are the most influential factors. Thus, the C4.5 algorithm can serve as an effective tool for boarding school management to improve the quality of educational services and the learning environment for students.